"Food waste-wastewater-energy/resource" nexus: Integrating food waste management with wastewater treatment towards urban sustainability. (1st March 2022) - Zan, Feixiang; Iqbal, Asad; Lu, Xiejuan; Wu, Xiaohui; Chen, Guanghao
Highlights: The concept of "food waste-wastewater-energy/resource" nexus was proposed. The comprehensive impacts of food waste diversion were reviewed and analysed. The major challenges of food waste diversion were discussed from five aspects. Food waste diversion could facilitate sustainable food waste management. Abstract: Sustainable food waste management is a global issue with high priority for improving food security and conserving natural resources and ecosystems. Diverting food waste from the solid waste stream to the wastewater stream is a promising way for food waste source separation, collection, treatment, and disposal. Given the advances in wastewater treatment, this integrated system has great potential for the concurrent recovery of water, resource, and energy. To this end, many efforts from lab-scale to full-scale studies have been devoted to evaluating the feasibility and associated impacts on both solid waste and wastewater systems. This paper summarizes the current status of food waste diversion from the aspects of principle and application. The impacts of food waste diversion on solid waste treatment, sewer system, wastewater treatment, and environmental benefits have been comprehensively reviewed and analysed. In the context of the critical review, this paper further identified the challenges of food waste diversion in unified definitions of the field, sewer network assessment, emerging wastewater treatment technologies, scale-up studies, and policy drivers. Perspectives on the contribution of food waste diversion to a food waste management hierarchy were discussed for initiating the nexus of "food waste-wastewater-energy/resource". We conclude that food waste diversion could facilitate sustainable urban development, but the area-specific factors (e.g., household practices, water resource, sewerage system condition, and treatment techniques) require adequate evaluations to determine the implementation. The outcomes of this study could contribute to the practice and policy-making of food waste management towards urban sustainability. Graphical abstract: Image, graphical abstract .